Dukungan keluarga dan kepatuhan minum obat penderita tuberkulosis paru - Rika Amran; Dessy Abdullah; Rendri Bayu Hansah; Naima Lessie; Eko Perdana Putra (Holistik Jurnal Kesehatan, 2023)
Background: The patient's adherence to taking medications is an important factor in the success of the treatment of pulmonary tuberculosis. The high number of dropouts resulted in high cases of drug resistance, namely multi-drug resistance.Purpose: To analyze the relationship between family support to adherence to taking medications for people with pulmonary tuberculosis.Method: Quantitative with analytic cross-sectional design. The population in this study was all pulmonary tuberculosis patients. The total sample in this study was 168 respondents consisting of 84 case groups and 84 control groups. The sampling technique used is consecutive sampling. The instrument used is a questionnaire. The statistical test used is chi-square.Results: Finding that there was a significant relationship between family support and adherence to taking medications for people with pulmonary tuberculosis (p = 0.003 and OR 2.956).Conclusion: People who lack support from family are 2.9 times more likely to be disobedient to taking medication than people who get support from family.Suggestion: It is expected to provide health education to the family and closest people of Pulmonary TB sufferers so that they can participate in reminding and motivating sufferers.Keywords: Pulmonary tuberculosis; Anti-Tuberculosis Drugs (ATD); Adherence; Family support.Pendahuluan: Kepatuhan pasien dalam minum obat merupakan faktor penting dalam keberhasilan suatu pengobatan tuberkulosis paru. Tingginya angka putus berobat mengakibatkan tingginya kasus resisten obat yaitu multi drug resistance.Tujuan: Untuk menganalisa hubungan dukungan keluarga dengan kepatuhan minum obat penderita tuberkulosis paru.Metode: Penelitian ini menggunakan desain kasus kontrol. Populasi dalam penelitian ini ialah seluruh pasien tuberkulosis paru. Jumlah sampel pada penelitian ini sebanyak 168 responden yang terdiri dari 84 kelompok kasus dan 84 kelompok kontrol. Teknik sampling yang digunakan adalah consecutive sampling. Instumen yang digunakan adalah kuesioner. Uji statistik yang digunakan adalah chi square.Hasil: Didapatkan ada hubungan yang signifikan antara dukungan keluarga dengan kepatuhan minum obat penderita tuberkulosis paru (p=0,003 dan OR 2,956).Simpulan: Orang yang kurang mendapatkan dukungan dari kelurga berpeluang 2,9 kali lebih besar tidak patuh minum obat dibandingkan dengan orang yang mendapatkan dukungan dari keluarga.Saran: Diharapkan memberikan pendidikan kesehatan kepada kepada keluarga dan orang terdekat penderita TB Paru agar dapat ikut serta mengingatkan dan memberikan motivasi pada penderita.